INTERVENSI SOSIAL CATCALLING SEBAGAI BENTUK PELECEHAN SEKSUAL - Arjun Rojalio Hibrizi; Ahmad Rizaldi Sutomo, Cindi Indriani, Rahma Salsa Nabila, Yemima Priscila Barutu, Rijal Abdillah (ADISAM PUBLISHER, 2025)
This study aims to identify the prevalence, impact, and intervention of the catcalling phenomenon experienced by female students at Universitas Bhayangkara Jakarta Raya. Catcalling is a form of verbal sexual harassment commonly occurring in campus environments and can cause significant psychological impacts on the victims. This study combines interview, observation, and psychoeducational intervention methods to gather comprehensive data on the issue. Based on interviews with 20 female students, it was found that 70% of them had experienced catcalling, both on campus and while commuting. Additionally, 60% of the victims chose not to report the incidents due to uncertainty about the steps to take and fear of social repercussions. In the observation conducted in campus areas, catcalling behaviors were frequently found near parking lots, canteens, and main corridors. The psychoeducational intervention provided through educational materials and group discussions successfully increased the students' understanding of catcalling as a form of sexual harassment and encouraged them to report such incidents. Before the intervention, only 30% of participants understood catcalling as sexual harassment, but after the intervention, this figure increased to 85%. This study concludes that catcalling is an issue that requires serious attention from the campus authorities, and there is a need for more intensive policies and education to create a safe and inclusive environment for all individual